Bimetallic Pd/Sn-based nanoparticles and their catalytic properties in the semihydrogenation of diphenylacetylene - Dietrich, Christine; Chen, Si; Uzunidis, Georgios; Hähsler, Martin; Träutlein, Yannick; Behrens, Silke (ChemistryOpen, 2021)
Multimetallic nanoparticles often enhance the catalytic performance of their monometallic counterparts by increasing reaction rates, catalyst selectivity, and/or stability. A prerequisite for understanding structure- and composition-associated properties, however, is the careful design of multimetallic nanoparticles with various structures and compositions. Here, bimetallic Pd/Sn-based nanoparticles are prepared with a tunable composition and structure exploiting ionic liquids (ILs) as reaction medium (i. e., methyltrioctylammonium bis(trifluoromethylsulfonyl)imide). The nanoparticles are obtained in a one-pot synthetic procedure by reducing the metal salt precursors with triethylborohydride in the IL. The results show that the reaction parameters, in particular the nature and ratio of the Pd2+/Sn2+ precursors as well as the reaction temperature, influence NP formation and composition. X-ray diffraction with Rietveld analysis and transmission electron microscopy are employed to determine NP size and phase composition. Under optimized reaction conditions Pd2Sn or PdSn nanocrystals are formed as single-phase products after introducing an additional annealing step at 200 °C. Nanocrystals with intermetallic composition reveal enhanced catalytic properties in the semihydrogenation of diphenylacetylene which was used as a model reaction.
Gesehen am 04.08.2021